PEMBERIAN LAYANAN PRIORITAS DI RUMAH SAKIT BAGI PENYANDANG DISABILITAS MELALUI SiAPDi - Argo Wibowo; Antonius Rachmat Chrismanto; Rosa Delima (Universitas Sanata Dharma, 2021)
The presence of a hospital information system as a public facility must be as friendly as possible for patients. Patients can easily access the services provided by the hospital. Unfortunately, not all patients can easily access the service. Patients with disabilities often do not get priority when registering at the hospital. Although it has been delivered and given facilities for it, there are still people who use them unwisely. FTI UKDW, in collaboration with Panti Waluyo Purworejo Hospital, built a mobile-based priority queuing system called SiAPDi (Disability Priority Queue System). This system will help patients with disabilities have direct access to check registrations. Patients with disabilities can go directly to the clinic through this system without the need to pass the registration queue. The stage of making this system is divided into two, namely the first stage of making and adjusting the program, and the second stage of application testing. The program adjustment phase is done remotely because of the covid19 outbreak, and testing on users is also done remotely assisted by hospital staff. In using the application, users only need to choose a doctor, check date, and practice session to examine a hospital polyclinic.